As Simple as Possible, as Complex as Necessary: An approach to the design and development of web-based learning environments - Halliwell, Julian (Proceedings of the International Conference on Networked Learning, 2000)
The Internet and its associated technologies have proved serendipitously to be able to offer the universal network platform upon which to build Illich’s longed for "educational web" (Pickering, 1995). Instead of having to be content with the cost and limitations of discrete experimental infrastructures, developers of networked learning have been presented with a ready-made means of translating theory very rapidly into practice and of realizing their goal of new, potentially global teaching and learning environments based on accessibility, flexibility, empowerment, alternative modes of communication and so on. Amidst the excitement of this unexpected achievement, however, it is easy to forget that the Internet was not designed for the purposes of mass participation to which it is now being put. Ordinary users - people without technical computing expertise of any kind - were very far from the minds of the Internet pioneers who could not have envisaged the outcome of their project. Email and the web have been successful amongst other reasons because: 1) they are genuinely and profoundly useful; 2) they have been developed in an ’’open source’’ spirit of universal access and standardization; and 3) by and large they work. On the other hand their success is most certainly not due to their inherent simplicity: they are far from being as straightforward to use as say a toaster, a telephone or even a television set. Whilst acknowledging and welcoming the success of the Internet, and the web in particular, we should also recognize that this has been in spite of the fact that it is fundamentally complex as a system compared with the mass appliance technologies with which most people are familiar. This recognition should lead us, as both educational and technical developers of internet-based learning, to pay closer attention to counter-balancing the underlying userunfriendliness of our adopted medium by placing greater value on simplicity and usability. Unfortunately, although ordinary users frequently appreciate these qualities, both pedagogical and technical designers (not to mention managers and decision makers) tend to place greater importance on having sophisticated, comprehensive and "cutting edge’’ functionality, without considering fully whether the resulting systems are appropriate or will ultimately be effective. In this paper I will argue for greater emphasis to be placed upon simplicity as a key value in educational and technical design for web-based learning in the interests of achieving systems that are adequate, appropriate and effective. I will suggest that this approach is likely to lead more often to choices about what to leave out of the design rather than what to include. Complexity is not excluded, indeed it will often be unavoidable if the system is to be adequate, but it must be properly justified in the context in which the system is being developed and must not unnecessarily compromise effectiveness.